Determination Of Delta 13c Values Of Amphetamine And Methamphetamine Using Gas Chromatography/ Combustion/ Isotope Ratio Mass Spectrometry (Gc/C/Irms) - Obaid, Nayla Hilal M H (2013)
Drug abuse of amphetamine-type stimulants (ATS) has been considered as the most widespread problem around the world and also regarded as a threat to national security. This study is focused on stable carbon isotope analysis by isotope ratio mass spectrometry (IRMS) to develop and validate a method for amphetamine and methamphetamine analysis. The ability to measure isotope distribution in natural abundance with high accuracy and precision has increased the application of gas chromatography/combustion/isotope ratio mass spectrometry (GC/C/IRMS) for various applications in recent years. Urine Samples spiked with amphetamine and methamphetamine standards were extracted using liquid–liquid extraction and subsequently, reconstituted with the mobile phase for further purification and separation using High Performance Liquid Chromatography (HPLC). These fractions were collected and analysed using the GC/C/IRMS. GC/C/IRMS showed δ13C value of -24.72 ±0.6‰ and -28.90 ±0.15‰ for amphetamine methamphetamine, respectively. The solid samples of the same amphetamine and methamphetamine standards were also analysed to determine the δ13C of each standard by using the FLASH elemental analyzer isotope ratio mass spectrometry (EA/IRMS); these were then compared with the results obtained from the GC/C/IRMS. EA/IRMS showed comparable results with those obtained with GC/C/IRMS; amphetamine showed the δ13C value of -24.90 ±0.03‰, while methamphetamine showed δ13C result of -28.99 ±0.03‰.